Effects of Exercise Modes on Neural Processing of Working Memory in Late Middle-Aged Adults: An fMRI Study - Chen, Feng-Tzu; Chen, Ya-Ping; Schneider, Stefan; Kao, Shih-Chun; Huang, Chih-Mao; Chang, Yu-Kai (Frontiers in Aging Neuroscience, 2019)
Recent studies have highlighted the importance of regular exercise on cognitive function in aging populations, with aerobic exercise and cardiovascular fitness having received largest amount of research attention. However, whether exercise mode and cognitive function underlying behavioral modification and neural activation remains unknown. The present study therefore sought to examine the associations between different exercise modes and the working memory aspect of executive function as well as its task-evoked brain activation in the late middle-aged population. Seventy late middle-aged adults were classified into open-skill, closed-skill, or irregular exercise groups based on their participation in exercise activities prior to the study and then performed a spatial working memory task while undergoing functional magnetic resonance imaging scanning. The results revealed that exercise groups, regardless of exercise modes, showed better spatial working memory and physical fitness performance. Additionally, the open-skill group exhibited greater brain activation in the prefrontal lobe, anterior cingulate cortex/supplementary motor area, and hippocampus than those in the closed-skill group, suggesting a mode-sensitive compensatory mechanism in late middle-aged adults. These findings indicate that exercise promotes cognitive health, improves working memory, and enhances neurocognitive scaffolding in late middle-aged adults and further suggest that various exercise modes can effectively modulate frontal and hippocampal function in the face of age-related neurocognitive declines, implications that may inform the development of exercise programs for the elderly.